PENGARUH BEBAN PAJAK TANGGUHAN, PERENCANAAN PAJAK DAN PENGHINDARAN PAJAK TERHADAP MANAJEMEN LABA - Istiana Dewi, Putri; Djohar, Chaidir (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine : (1) The Effect of Deferred Tax Burden on Profit Management, (2) The Effect of Tax Planning on Profit Management (3) The Effect of Tax Avoidance on Profit Management.This type of research is quantitative associative and the analysis method used in this study is using panel data regression using Eviews 12 which consists of descriptive statistical analysis, selection of panel data model techniques, selection of panel data analysis models, classical assumption tests and hypothesis tests. The population of this study is Consumer Non-Cyclicals Sector Companies listed on the Indonesia Stock Exchange in 2017-2021. The research analysis was conducted on 99 Consumer Non-Cyclicals Sector Companies listed on the Indonesia Stock Exchange. By using purposive sampling, 32 company samples were obtained for 5 years so that the data obtained were 160 observational data from 32 multiplied by 5. The results of this study show that deferred tax burden has a significant positive effect on profit management, tax planning has a significant effect on profit management, tax avoidance has a significant effect on profit management.